The diagnosis of microorganism involved in infective endocarditis (IE) by polymerase chain reaction (PCR) and real‐time PCR: A systematic review. Issue 2 (24th October 2017) - Faraji, Reza; Behjati‐Ardakani, Mostafa; Moshtaghioun, Seyed Mohammad; Kalantar, Seyed Mehdi; Namayandeh, Seyedeh Mahdieh; Soltani, Mohammadhossien; Emami, Mahmood; Zandi, Hengameh; Firoozabadi, Ali Dehghani; Kazeminasab, Mahmood; Ahmadi, Nastaran; Sarebanhassanabadi, Mohammadtaghi
Abstract: Broad‐range bacterial rDNA polymerase chain reaction (PCR) followed by sequencing may be identified as the etiology of infective endocarditis (IE) from surgically removed valve tissue; therefore, we reviewed the value of molecular testing in identifying organisms' DNA in the studies conducted until 2016. We searched Google Scholar, Scopus, ScienceDirect, Cochrane, PubMed, and Medline electronic databases without any time limitations up to December 2016 for English studies reporting microorganisms involved in infective endocarditis microbiology using PCR and real‐time PCR. Most studies were prospective. Eleven out of 12 studies used valve tissue samples and blood cultures while only 1 study used whole blood. Also, 10 studies used the molecular method of PCR while 2 studies used real‐time PCR. Most studies used 16S rDNA gene as the target gene. The bacteria were identified as the most common microorganisms involved in infective endocarditis. Streptococcus spp. and Staphylococcus spp. were, by far, the most predominant bacteria detected. In all studies, PCR and real‐time PCR identified more pathogens than blood and tissue cultures; moreover, the sensitivity and specificity of PCR and real‐time PCR were more than cultures in most of the studies. The highest sensitivity and specificity were 96% and 100%, respectively. The gram positive bacteria were the most frequent cause of infective endocarditis. The molecular methods enjoy a greater sensitivity compared to the conventional blood culture methods; yet, they are applicable only to the valve tissue of the patients undergoing cardiac valve surgery.